STUDY ON DRAG REDUCTION PERFORMANCE OF RAKE FACE TURNING TOOL WITH VARIABLE CURVATURE SURFACE CONFIGURATION - CHEN XiaoFeng; XIE Feng; LEI XiaoBao; GENG Lin (Jixie qiangdu)
In order to reduce the resistance in the cutting process, through the configuration analysis of the tooth rake face of beaver, a turning tool with variable curvature quasi-linear surface configuration was designed. In 0. 15-0.5 mm back cutting ,four kinds of rake face configurations were selected for simulation cutting comparative analysis. The simulation results show that the cutting force of the rake face tool with chord function quasi-linear configuration is reduced by 3.5%-11.96% compared with the other rake face tools. The simulation results are verified by the right angle cutting experiment. Subsequently, the parameter optimization of cosine quasi-line function was carried out through simulation experiment, and the variation law of cutting force with the change of period and amplitude was obtained. The optimization results show that the drag reduction effect is the most obvious when the ratio of the back cutter amount to the front cutter area chord function is about 40% in one cycle. The variable curvature rake face turning tool designed in this study not only effectively reduces the cutting force, but also provides a new idea for the configuration design of metal cutting tools, which has strong application value.